Generation of miniploid cells and improved natural transformation procedure for a model cyanobacterium Synechococcus elongatus PCC 7942 - Riaz, Sadaf; Jiang, Ying; Xiao, Meng; You, Dawei; Klepacz-Smółka, Anna; Rasul, Faiz; Daroch, Maurycy (Frontiers in Microbiology, 2022)
Biotechnologically important and naturally transformable cyanobacterium, Synechococcus elongatus PCC 7942, possesses multiple genome copies irrespectively to its growth rate or condition. Hence, segregating mutations across all genome copies typically takes several weeks. In the present work, Synechococcus 7942 cultivation on a solid growth medium was optimised using different concentrations of agar, the addition of antioxidants and overexpression of catalase gene to facilitate rapid acquisition of colonies and fully segregated lines. Synechococcus 7942 was grown at different temperatures and nutritional conditions. The miniploid cells were identified using flow cytometry and fluorimetry. The natural transformation was carried out using miniploid cells and validated with PCR and HPLC. We identified that 0.35% agar concentration and 200 IU of catalase could improve the growth of Synechococcus 7942 on a solid growth medium. Furthermore, overexpression of a catalase gene enhanced the growth rate and supported diluted culture to grow on a solid medium. Our results revealed that high temperature and phosphate-depleted cells contain the lowest genome copies (2.4 ±0.3 and 1.9 ±0.2) and show the potential to rapidly-produce fully segregated mutants. In addition, higher antibiotic concentrations improves the selection of homozygous transformants while maintaining similar genome copies at a constant temperature. Based on our observation, we have an improved cultivation and natural transformation protocol for Synechococcus 7942 by optimising solid media culturing, generating low ploidy cells that ultimately reduced the time required for the complete segregation of engineered lines.